OPEFB Filler from Biomass in Superabsorbent Polymer Composite for Agriculture Application: A Comparative Study - Wan Siti Nadiah, Wan Yaacob; Saidatul Shima, Jamari; Suriati, Ghazali (Springer Singapore, 2014)
An agriculture activity is one of the major sectors which contribute a significant share to Malaysia economy. Therefore it is important to maintain the soil fertility. Superabsorbent polymer composite (SAP’c) was produced using graft polymerization technique with the addition of the oil palm empty fruit bunch (OPEFB) filler to enhance the absorbance properties and decomposition process. Effect of filler addition at different size to the SAP’c was investigated. Water absorbency test was conducted to determine the absorbency and swelling properties while Fourier Transform Infrared (FTIR) and Scanning Electron Microscopic (SEM) analysis was conducted to investigate the functional groups and morphology of the SAP’c. Water absorb highest for SAP’c with coarse OPEFB while fine particle size showed a decrement in swelling behaviour. FTIR spectra shows that –C ≡ C–H with C–H bend existed in all samples. SEM showed that the addition of the OPEFB give a fibrous morphology and build a surface contact. In conclusion the addition of biomass filler in the superabsorbent polymer (SAP) will increase the water absorbency and swelling properties of the hydrogel.